(untitled) (Hekima Review, 2006)
Challenges and prospects of the Church in Africa: Theological reflection of the 21st Century is the title of the first book in a series of publication done by the Ecumenical Symposium of Eastern Africa Theologians (ESEAT). It investigates various features of African Christianity and points out the different challenges and prospects facing the Church in Africa in the 21st century. The contributors search for new theological insights, which could help to interpret the gospel in ways that are relevant to the African context.